Poorer clinical outcomes of early‐onset peritonitis in elderly peritoneal dialysis patients: A longitudinal and multicenter study. Issue 4 (1st December 2021) - Guo, Qiaoyan; Chen, Yangyang; Wu, Ren; Yang, Liming; Zhu, Xueyan; Zhao, Qiao; Zhuang, Xiaohua; Wu, Yanfeng; Luo, Ping; Cui, Wenpeng
Abstract: Introduction: Early‐onset peritonitis (EOP) is a risk factor for mortality in peritoneal dialysis (PD) patients. This study investigates the clinical features and outcomes of EOP in elderly patients. Methods: This multicenter retrospective study evaluated 433 elderly PD patients with end‐stage renal disease. The cohort was divided into nonperitonitis group (n = 239), EOP group (≤12 months, n = 109) and late‐onset peritonitis (LOP) group (>12 months, n = 85). Clinical data, treatment results, and outcomes were compared between the groups. Results: Compared with LOP group, there were no significant intergroup differences in the rate of primary recovery, complete cure, relapse, catheter removal, or death from PDAP ( p >0.05) in the most recent PDAP episode. However, Kaplan–Meier analysis showed that patients in the EOP group were likely to have multiple episodes of PD‐associated peritonitis (PDAP), technique failure, all‐cause death, and composite endpoint in the long‐term prognostic outcomes ( p <0.001). Conclusions: EOP is significantly associated with poorer clinical outcomes in older PD patients.